Divining Margaret Laurence : a study of her complete writings - Stovel, Nora Foster, 1942- (McGill-Queen's University Press, 2008)
Margaret Laurence is justly famous for her Manawaka cycle of Canadian novels, but her work extends from Canada to Africa and includes poetry and prose, children's and adult literature, memoir and travel-writing. Whereas previous studies focus on certain aspects of her work, Divining Margaret Laurence addresses all her important writings, including a final, unfinished manuscript - "Dance on the Earth: A Memoir." This comprehensive study of her writings, including archival material, allows Nora Stovel to trace the development of Laurence's Canadian identity, feminist sympathies, moral vision, and creative artistry. Twenty years after her death Margaret Laurence remains one of Canada's most esteemed and beloved writers. This new critical assessment of her work is not only a testament to her literary achievement but also a valuable contribution to Canadian, African, women's, children's, travel, and fiction writing